Drug-resistant tuberculosis in HIV-infected patients in a national referral hospital, Phnom Penh, Cambodia - Genevieve Walls; Sophie Bulifon; Serge Breysse; Thol Daneth; Maryline Bonnet; Northan Hurtado; Lucas Molfino (Taylor & Francis Group, 2015)
Background and objective: There are no recent data on the prevalence of drug-resistant tuberculosis (DR TB) in Cambodia. We aim to describe TB drug resistance amongst adults with pulmonary and extra-pulmonary TB and human immunodeficiency virus (HIV) co-infection in a national referral hospital in Phnom Penh, Cambodia. Design: Between 22 November 2007 and 30 November 2009, clinical specimens from HIV-infected patients suspected of having TB underwent routine microscopy, Mycobacterium tuberculosis culture, and drug susceptibility testing. Laboratory and clinical data were collected for patients with positive M. tuberculosis cultures. Results: M. tuberculosis was cultured from 236 HIV-infected patients. Resistance to any first-line TB drug occurred in 34.7% of patients; 8.1% had multidrug resistant tuberculosis (MDR TB). The proportion of MDR TB amongst new patients and previously treated patients was 3.7 and 28.9%, respectively (p<0.001). The diagnosis of MDR TB was made after death in 15.8% of patients; in total 26.3% of patients with MDR TB died. The diagnosis of TB was established by culture of extra-pulmonary specimens in 23.6% of cases. Conclusions: There is significant resistance to first-line TB drugs amongst new and previously treated TB-HIV co-infected patients in Phnom Penh. These data suggest that the prevalence of DR TB in Cambodia may be higher than previously recognised, particularly amongst HIV-infected patients. Additional prevalence studies are needed. This study also illustrates the feasibility and utility of analysis of non-respiratory specimens in the diagnosis of TB, even in low-resource settings, and suggests that extra-pulmonary specimens should be included in TB diagnostic algorithms.